A New Rule : The Swiss Debt Brake - Danninger, Stephan (IMF Working Papers; Working Paper ;, 2002)
The paper provides an international comparison and a comprehensive analysis of a new fiscal expenditure rule for the federal government in Switzerland. The proposed rule has two innovative features: it aims at a structurally balanced budget in the short-run by annually setting a cyclically adjusted expenditure ceiling, and it arrests the accumulation of public debt via corrections of future expenditure targets for past deviations from projected fiscal balances. The paper finds that the new rule is likely to reduce procyclical tendencies in fiscal policy and that its objectives are adequate in meeting long-run fiscal challenges arising from demographic changes.